[Pegylation and interferons in multiple sclerosis] - Diego Centonze (Farmeconomia: Health Economics and Therapeutic Pathways, 2016)
Pegylation is a procedure used for drug development since the 1970s and consists of the conjugation of a polyethylene glycol molecule (PEG) to a drug. PEG has shown to be safe and effective in improving the pharmacokinetic and pharmacodynamic profile of drugs. Recently, a 20 kDa linear chain of PEG was conjugated to interferon beta-1a with the aim to offer a new treatment option to relapsing-remitting multiple sclerosis (RRMS) patients. Due to a prolonged bioavailability, this new drug can be administered less frequently (every two weeks) than the other interferons beta available, thus allowing to hypothesize a better adherence to the treatment, which, in turn, should result in better clinical and economic outcomes. A phase III clinical trial has proven its effectiveness compared to placebo in RRMS patients, as well as a safety profile comparable to that found in other interferon beta preparations. The immunogenicity of this new molecule is < 1%, thus minimizing the suppression or reduction of interferon beta biological activity that could come from the development of Neutralizing Antibodies (NAbs).